2009
DOI: 10.1007/s10532-009-9321-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gasoline components on MTBE and TBA cometabolism by Mycobacterium austroafricanum JOB5

Abstract: In this study we have examined the effects of individual gasoline hydrocarbons (C(5-10,12,14) n-alkanes, C(5-8) isoalkanes, alicyclics [cyclopentane and methylcyclopentane] and BTEX compounds [benzene, toluene, ethylbenzene, m-, o-, and p-xylene]) on cometabolism of methyl tertiary butyl ether (MTBE) and tertiary butyl alcohol (TBA) by Mycobacterium austroafricanum JOB5. All of the alkanes tested supported growth and both MTBE and TBA oxidation. Growth on C(5-8) n-alkanes and isoalkanes was inhibited by acetyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…These enzymes are again potentially directly associated with the alkane-oxidizing activity of this strain. We have also recently demonstrated that MTBE can be oxidized by strain JOB5 after growth on most shorter chain (< C 8 ) normal and branched alkanes (House & Hyman, 2010). These physiological studies suggest that the same monooxygenase enzyme initiates the oxidation of MTBE, TBA, and all of the growth-supporting ≤ C 8 alkanes.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations
“…These enzymes are again potentially directly associated with the alkane-oxidizing activity of this strain. We have also recently demonstrated that MTBE can be oxidized by strain JOB5 after growth on most shorter chain (< C 8 ) normal and branched alkanes (House & Hyman, 2010). These physiological studies suggest that the same monooxygenase enzyme initiates the oxidation of MTBE, TBA, and all of the growth-supporting ≤ C 8 alkanes.…”
Section: Introductionmentioning
confidence: 69%
“…Cells grown on all of the alkanes tested consumed all of these ethers and, in most instances, this activity was strongly inhibited (>90 percent) by the presence of acetylene (Exhibit 1). This effect of acetylene suggested the ethers were all oxidized by SCAM (House & Hyman, 2010). The role of SCAM activity in ether oxidation is further supported by the much lower levels of ether-oxidizing activity in cells grown on dextrose-containing medium (Exhibit 1).…”
Section: Cometabolic Oxidation Of Cyclic Ethers By Resting Cellsmentioning
confidence: 88%
See 2 more Smart Citations
“…A pure culture designated PEL-B201 co-metabolized MTBE following growth on benzene; however, MTBE degradation was severely inhibited in the presence of benzene at concentrations as low as 0.15 mg l À1 presumably due to competitive inhibition (Koenigsberg et al, 1999). Benzene and ethylbenzene have also been shown to inhibit MTBE oxidation in an alkane-grown pure culture of Mycobacterium austroafricanum JOB5 (House & Hyman, 2010). In contrast, other investigations of interactions between BTEX and MTBE in continuous reactors and mixed bacterial consortia showed no impacts of BTEX compounds on MTBE degradation (Pruden et al, 2001;Sedran et al, 2002).…”
Section: Introductionmentioning
confidence: 97%